2021
DOI: 10.1021/acs.jmedchem.1c00362
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cephalosporin Conjugates Display Potent and Selective Inhibition of Imipenemase-Type Metallo-β-Lactamases

Abstract: In an attempt to exploit the hydrolytic mechanism by which β-lactamases degrade cephalosporins, we designed and synthesized a series of novel cephalosporin prodrugs aimed at delivering thiol-based inhibitors of metallo-β-lactamases (MBLs) in a spatiotemporally controlled fashion. While enzymatic hydrolysis of the β-lactam ring was observed, it was not accompanied by inhibitor release. Nonetheless, the cephalosporin prodrugs, especially thiomandelic acid conjugate ( 8 ), demonstrated pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The pairing of BP1 with meropenem in combination therapy has the potential to be a favorable solution since both antimicrobials work synergistically to target the MBL and the pathogen (Table ). Martin and co-workers also attached a chelator to a cephalosporin as a potential MBLI, however, their BL acts as a prodrug and upon hydrolysis releases a zinc binding thiol moiety to the enzyme active site. Their MIC data indicates that higher concentrations (≥32 mg/L) of their most potent compounds are required to resensitize the clinical isolates to meropenem, with the compounds having more activity towards bacteria expressing imipenemase (IMP) MBLs in comparison to VIM and NDM. , It should be noted that BP1 is active against IMP, NDM, and VIM MBLs at lower concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pairing of BP1 with meropenem in combination therapy has the potential to be a favorable solution since both antimicrobials work synergistically to target the MBL and the pathogen (Table ). Martin and co-workers also attached a chelator to a cephalosporin as a potential MBLI, however, their BL acts as a prodrug and upon hydrolysis releases a zinc binding thiol moiety to the enzyme active site. Their MIC data indicates that higher concentrations (≥32 mg/L) of their most potent compounds are required to resensitize the clinical isolates to meropenem, with the compounds having more activity towards bacteria expressing imipenemase (IMP) MBLs in comparison to VIM and NDM. , It should be noted that BP1 is active against IMP, NDM, and VIM MBLs at lower concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…32 An area gaining traction is the employment of BL conjugates as prodrugs and inhibitors, forming a relatively stable enzymehydrolyzed product complex to target the MBL. 21,33,34 In this study, our novel approach was to covalently attach a wellbinding metal/zinc chelator to a BL scaffold (cephalosporin) in order to improve selectivity and biodistribution of the chelator. This approach gives both compounds an equal chance to reach the bacterial cell wall-producing target enzymes, thereby providing a lethal duo of high specificity to eradicate the bacterial infection.…”
mentioning
confidence: 99%
“…However, DBO and VAB do not inhibit any metallo-carbapenemases. Compared with the clinical success of SβL inhibitors, there are no equivalent inhibitors in the clinic for MβLs, which can hydrolyze almost all β-lactams including carbapenems and the first-generation β-lactamase inhibitors clavulanate, tazobactam, and sulbactam. ,, The continuous emergence and dissemination of MDR Gram-negative pathogens with acquired serine and metallo-carbapenemase genes has led to an urgent need for the development of broad-spectrum, dual-action inhibitors to conquer carbapenem resistance. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a report from Hu and colleagues earlier this year disclosed a new class of MBLIs featuring a unique trans- cephalosporin scaffold (Figure ). We previously described a report using a similar scaffold for development of BlaC-selective fluorogenic probes; the authors discovered that this stereochemistry significantly impaired turnover by NDM-1 and postulated that this scaffold could be combined with a 3′-thiobenzoyl substituent (previously demonstrated to inhibit NDM-1 with conventional cephalosporins) to achieve more potent inhibitors of MBLs. Mechanistic evaluation of the inhibitor library suggested that activity correlated with more electronegative groups at the C-3′ position; subsequent X-ray crystallography studies confirmed the inhibitor forms a stable complex with NDM-1 following hydrolysis and subsequent elimination of the leaving group, with the imine nitrogen and trans C-7 alkoxy group both forming important interactions with active site residues …”
Section: Antibiotics: Lactam Conjugates As Pro- and Co-drugsmentioning
confidence: 98%